Factors Associated with Medical Students’ Performance in Blueprint-based Online Formative Assessment - Najla Nabila; Yulistini; Ilmiawati; Firdawati; Rahma Tsania Zhuhrah; Rahmani Welan (PT Inovasi Pratama Internasional, 2026)
Formative assessments had been carried out amidst the changes that have occurred during the COVID-19 pandemic. Medical students must be adapted to change in the teaching and learning process from in-person learning to online learning. This research aimed to determine pre-clinical students' weaknesses in terms of the results of formative assessments based on question blueprints (UTB I) and to find out whether gender, admission pathway, or learning methods can influence the results of formative assessments. A cross-sectional study was performed on the exam results of 711 medical students who undertook UTB I exam. The instrument of this research was secondary data. Gender, admission pathway, and learning methods were analyzed using an independent t-test and One-way ANOVA.The research showed that the median correct answer on UTB I was less than 50%. There was no significant difference in the mean formative assessment score between the male and female groups (p=0.743). It was found that at least two groups had significant differences UTB I scores based on admission pathways (p<0.001). Based on the learning method, the results indicate significant differences between in-person learning and online learning (p<0.001).